Optimization of Dutch Bucket Method in Melon (Cucumis melo L.) Plant Culture with Variations of Nutrition, Bucket, and Pruning: - - Anif Yuni Muallifah; Muhammad Ikhwan Ardiansyah; Budurul Fadhilah (Jurnal Ilmu Pertanian Indonesia, 2026)
This study aimed to evaluate the effects of nutrient concentration, bucket size, and pruning on the growth and yield of melon plants (Cucumis melo L.). The experiment was arranged using a completely randomized design (CRD) with a factorial design consisting of three factors: nutrient concentration (1500 and 2000 ppm), bucket size (large and small), and pruning (pruned and unpruned). The research stages included greenhouse sterilization, installation of a modified Dutch bucket system with four nutrient outlet holes, seedling, planting, maintenance, and harvesting. Data were analyzed using analysis of variance (ANOVA), followed by Tukey’s post hoc test at a 95% confidence level. The results showed that the modified Dutch bucket system functioned effectively, with efficient nutrient circulation. The environmental conditions in the greenhouse ranged from 31.3°C to 39.7°C, relative humidity from 30% to 59.3%, and light intensity from 2445.7 to 23651.7 lux. Nutrient concentration significantly affected plant height, leaf width, root fresh weight, fruit weight, fruit diameter, and fruit sweetness, whereas bucket size significantly influenced fruit weight, fruit diameter, and fruit sweetness. Pruning significantly affected only the plant height. The best treatment was 1500 ppm nutrient concentration using a large bucket without pruning, producing the highest values for leaf width (27.2 cm), root fresh weight (112.44 g), fruit weight (1517 g), fruit diameter (47 cm), and fruit sweetness (10.67 °Brix). These findings indicate that optimal nutrient concentration and bucket size are key factors for improving melon productivity under hydroponic conditions. Keywords: Cucumis melo L, Dutch bucket, greenhouse, hydroponics, nutrients